Diuretic and hypotensive effect of morelloflavone from Garcinia dulcis in two-kidneys-one-clip (2K1C) hypertensive rat - Nattaya Thongsepee,; Wilawan Mahabusarakam,; Siriphun Hiranyachattada, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Morelloflavone, a biflavonoid from Southeast Asian folk medical plant Garcinia dulcis, possesses powerful antioxidant activity both in vivo and in vitro. We aimed to evaluate the hypotensive and diuretic effect of morelloflavone in two-kidneys-one-clip (2K1C) renovascular hypertensive rats together with its vasorelaxant mechanism. Male Wistar rats (175±4 g) were undergone 2K1C and sham operation (SO) (n=6, each group). Four weeks after the rats were anesthetized and clearance markers (0.5% para-aminohippuric acid and 1% inulin) were given via a jugular vein (1.6 mL/h/100 g BW) to estimate renal blood flow (RBF) and glomerular filtration rate. The arterial blood pressure (AP) was monitored via a carotid artery and urine samples were collected. After equilibration, either morelloflavone or vehicle (DMSO) was given (0.1 mg/kg BW+5 μg/min/kg BW). Baroreflex sensitivity (BRS) (ΔHR/ΔMAP) was performed by an intravenous injection of 1, 2, 4, 8, 16 and 32 μg/kg BW phenylephrine (PE) or sodium nitroprusside. The PE-preconstricted isolated thoracic aortic rings (intact and denuded) relaxation were experimented using organ bath technique by cumulative additions of morelloflavaone (10-13-10-5 M) in the presence of specific vasorelaxant inhibitors and expressed as %relaxation from pre-contraction tension. In 2K1C rats, morelloflavone significantly lowered mean AP, increased RBF and increased urine flow rate when compared to vehicle control (138±6 vs. 152±1 mmHg, 3.44±0.49 vs. 2.29±0.25 mL/min/g KW and 42.0±9.4 vs. 18.2±3.9 μL/min/g KW, p<0.05), respectively and also restored the blunt BRS. Nitric oxide signaling pathway triggered by morelloflavone might be responsible for its diuretic and hypotensive effect.